2016
DOI: 10.1024/0301-1526/a000509
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of magnetic resonance angiography for acute pulmonary embolism - a systematic review and meta-analysis

Abstract: Abstract. Background: The aim of this meta-analysis was to evaluate the diagnostic accuracy of magnetic resonance angiography (MRA) for acute pulmonary embolism (PE). Methods: A systematic literature search was conducted that included studies from January 2000 to August 2015 using the electronic databases PubMed, Embase and Springer link. The summary receiver operating characteristic (SROC) curve, sensitivity, specificity, positive likelihood ratios (PLR), negative likelihood ratios (NLR), and diagnostic odds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Increasing technical development has made MRI less susceptible to these limitations. It has been suggested that MRI could emerge as a diagnostic option regarding APE, particularly in patients not suitable for CTPA (6,61). Nevertheless, MRI is not fully accepted yet as a diagnostic test in patients with suspected APE due to limited sensitivity (7,61).…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…Increasing technical development has made MRI less susceptible to these limitations. It has been suggested that MRI could emerge as a diagnostic option regarding APE, particularly in patients not suitable for CTPA (6,61). Nevertheless, MRI is not fully accepted yet as a diagnostic test in patients with suspected APE due to limited sensitivity (7,61).…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…However, the nature of numerous tissue air transitions and significant artifacts limit the use of traditional MRI in detection of small pulmonary emboli, 78 leading to concerns about sensitivity in detection. 79,80 The utility of Gadolinium enhanced MRI in clot detection was evaluated systematically in the PIOPED III study which demonstrated great specificity (99%) but low sensitivity (78%) and further highlighted the variations between centers in terms of the adequacy imaging acquired. 81 …”
Section: The Role Of Mri In Pementioning
confidence: 99%